Analisis Pengaruh Penambahan Koagulan Terhadap Kualitas Tetes Tebu dalam Proses Dekalsifikasi sebagai Bahan Baku Pembuatan Monosodium Glutamate - Shofia Khoirunissa, Dita; Ramadhani, Salsabila Amania; Darmayanti, Rizki Fitria; Muharja, Maktum; Khotimah, Husnul; Ayu Salsabila, Putri (Rekayasa, 2025)
One of the challenges in preparing MSG raw materials is the reduction in the quality of molasses due to changes in the sugar production process. This research aims to evaluate the impact of adding coagulants on improving the quality of molasses in the Industrial MSG preparation. The materials used consist of sugar cane molasses and Sodium polyacrylate with varying concentrations of 5-20 ppm. Analysis was carried out on the percentage of total solids (%TS) using the sludge reduction rate method, and by comparing the total solution volume with the sludge height. The results showed that the addition of coagulant had a significant effect on the rate of sludge formation. The optimum point was achieved by adding 20 ppm of coagulant, which was able to achieve sludge reduction stability within 0.5 hours. Optimal operational conditions occur at a temperature of 55℃, pH 2.5-2.6, and a sugar content of 37%. The important role of the coagulant solution volume was seen in accelerating the deposition process, which had a significant impact (P 0.1). Although this condition has the potential to accelerate improvements in the quality of molasses in the production process, it still requires an assessment of the economic impact on overall production profits. The addition of coagulants was identified as a solution to improve the quality of molasses which was decreasing.